Technology Acceptance Model for Reconstructing Al-Islam and Kemuhammadiyah Learning at Universitas Muhammadiyah Sumatera Utara - Fanreza, Robie; Daulay, Mahmud Yunus; Ginting, Nurman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to see the influence of Usability Perception, Ease of Use, Attitude, and Behavioral Intention on Technology-Based AIK Learning in Universitas Muhammadiyah Sumatera Utara. Technology is currently an indicator of the development of science. Currently, Universitas Muhammadiyah Sumatera Utara continues to try to develop technology-based learning media towards a world-class university. However, many students are still not maximized with running the technology prepared for teaching, especially in AIK courses. This study uses a quantitative approach, hypothesis testing, and the inner model obtained from data processing using SMART PLS. The conclusion are this study the t-statistic value for variable X1 (perceived usefulness) indicates that perceived convenience does not affect technology-based AIK learning, and the t-statistic value for variable X2 (Ease of Use) indicates that ease of use does not affect technology-based AIK learning. So, the t-statistic value for variable X3 (Attitude) indicates that attitude affects technology-based AIK learning. The t-statistic value for variable X4 (Behavioral Intention) indicates that Behavioral Intention affects technology-based AIK learning. The Technology Acceptance Model (TAM) explains how users accept and adopt technology based on two main factors: perceived usefulness and perceived ease of use. In the context of AIK learning at Universitas Muhammadiyah Sumatera Utara (UMSU), TAM plays a crucial role in shaping the effectiveness and efficiency of technology-based learning.